The Oxford handbook of management ideas - Sturdy, Andrew; Heusinkveld, Stefan; Reay, Trish; Strang, David (Oxford : Oxford University Press, 2019)
Management ideas, and their associated applications, have become a prevalent feature of our working lives. While their focus is familiar, such as efficiency, motivation, and improvement, they range from specific notions such as activity-based costing, to broad movements like corporate social responsibility. Providing an up to date, enduring, and authoritative account of the field of research on management ideas, this work addresses questions of where management ideas come from, how they are produced, promoted and used, and their effect on business and working practices.
Evolving management ideas / Hannele Seeck, Juha-antti Lamberg -- Management's gurus / David Collins -- Business media: From Gatekeeping to Transmediality / t Management ideas in everyday life / Philip Hancock, Melissa Tyler -- Changing the critique: From Critical Management Studies to Activist Scholarship / Craig Prichard, Ozan Alakavuklar -- Alternatives to management ideas / Martin Parker -- Management Ideas and the Social Construction of Organizations / Shawn Pope, Patricia Bromley -- The system of management ideas: Origins, Microfoundations, and Dynamics / Michael Mol, Julian Birkinshaw, Nicolai J. Foss -- New Directions For Research On Management Ideas / Andrew Sturdy, Stefan Heusinkveld, Trish Reay, David Strang -- The persistence of management ideas: How framing keeps 'lean' moving / Jos Benders, Marlieke van Grinsven, Jonas Ingvaldsen -- Management Techniques / Andreas Werr, Peter Walgenbach -- Professional Structures and Practice Change: Institutionalization Processes in Accounting and Strategy / Richard Whittington, Deborah Anderson -- The Lifecycle of Management Ideas: Innovation, Diffusion, Institutionalization, Dormancy, and Rebirth / Eric Abrahamson, Alessandro Piazza -- Methods for the Study of Management Ideas / David Strang, Christian Wittrock -- The philosophy of management ideas / Joe O'Mahoney.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 2, 2019).
Keywords: Management -- Philosophy